The Zakat in the Sahih Muslim. Essay on the mandatory alms and charity in Islam - López Brenes, Manuel Enrique (2016)
This essay analyzes the importance of the zakat as well as the different explanations concerning this term as they are contained in Prophet Muhammad’s Muslim tradition (Sunna). This paper studies the various Arabic sources, especially the Sahih Muslim compiled by Abu al-Husayn al-Qushayri al-Naysaburi Muslim b. al-Hajjaj (d. 875 c.e.). Zakat is the third pillar of Islam, which next to the shahada (profession of faith), the salat (praying), the sawm (fasting) during Ramadan, the ninth month of the Muslim calendar, and al-hajj (pilgrimage to Mecca) constitute the five pillars (arkan) of Islam. Zakat is the mandatory alms in Islam. It is also known as sadaqa. This is why in this essay these two terms are used meaning the same, since they appear this way in the various sources. Due to the fact that sadaqa also means charity, this term is used with this other meaning as well. Muslim in his Sahih Muslim compiled the ahadith (Prophet Muhammad’s sayings and deeds) concerning the mandatory paying of the zakat or sadaqa. In this essay these ahadith are analyzed, discussed in detail and compared with many others contained in the various Arabic-Muslim sources which also deal with this theme